Web-Based Application House Monitoring System Through Image Transfer - Hasan, Hamdi H. (2008)
Web Based Applications have benefited many people from all walk of life, by giving them access to information anytime, anywhere. This study presents a new web based application that enable people to monitor their houses from wherever they are, at any given time. The absence of working parents from their homes raised anxiety to many parties. Thus this application propose to install a webcam in a PC in the home, and design a web application which enables parents to browse and monitor their homes from any place. This application does not require professional users, regular users with minimum knowledge of using the internet should be able to learn the proposed system. This system is easy to be used, easy to be learned.